Clinical Performance of the LiquidArray® Gastrointestinal VER 1.0 Assay in Patients with Suspected Gastroenteritis - Sophie Jones; Kathleen Pheasant; Colette Dalton; Julie Green; Catherine Moore (Diagnostics)
Background/Objectives: Rapid and accurate pathogen identification is essential for the proper management of patients with infectious gastroenteritis, as well as for a better control of disease outbreaks. This observational, non-interventional, single-site study evaluated the diagnostic accuracy of LiquidArray® Gastrointestinal VER 1.0, a multiplex PCR syndromic panel capable of detecting up to 26 clinically relevant enteropathogens. Methods: Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and likelihood ratio (LR) were evaluated using stool samples from 1512 patients with suspected gastroenteritis and were compared to seven competitor assays. Results: LiquidArray® Gastrointestinal VER 1.0 showed a very low invalid rate (0.5% at initial testing, down to 0% after repeat) and high sensitivity (>90% for most detected targets) and specificity (>99% for all detected targets). Accordingly, the PPV and NPV were high (>90% for most targets and >99% for all targets, respectively). The analytical performance of LiquidArray® Gastrointestinal VER 1.0 was also excellent as to co-amplification capability, cross-reactivity and assay precision. Conclusions: This study demonstrates the excellent clinical performance of LiquidArray® Gastrointestinal VER 1.0 and its suitability for implementation in clinical routine for the rapid and accurate diagnosis of infectious gastroenteritis.